The Optimization of Teacher Performance Based on Transformational Leadership, Organizational Commitment and Organizational Culture - Sugeng, Sugeng (Technium Business and Management, 2022)
Teacher performance gives important contribution to maintain and improve educational quality. This research aimed to prove how transformational leadership directly influenced teacher performance or by way of organizational culture and organizational commitment. The research population was Secondary School teachers in Malang Regency. The Sample consisted of 128 people. The sampling method applied multistage random sampling. The data analysis technique was Structural Equation Modeling (SEM) – PLS. The research result condcluded that teacher performance could be improved by consistent implementation of transformational leadership and by strengthening orgarnizational culture and organizational commitment. In addition, the role of organizational culture and organizational commitment as the mediating variables was proven to be positive and significant.